Anatomi Kepemimpinan Ambidextrous: Eksplorasi Peran Algoritma People Analytics dan Kecerdasan Emosional dalam Meningkatkan Agile Performance Tim Lintas Fungsi (Az-Zaida: Jurnal Ilmu Multidisiplin, 2026)
This study aims to gain an in-depth understanding of the daily professional experiences (phenomenology) of Critical Description Troops related to the unique HR challenges they face. Its primary function is to interpret how the phenomenon of Hyper-Vigilance (extreme vigilance) affects work-life balance and shapes their construct of the Psychology of Trust towards their organization and coworkers. The research used a Narrative and Phenomenological Study based on semi-structured in-depth interviews with 20 key personnel from intelligence and cybersecurity units. Qualitative data were analyzed using Thematic Analysis to identify key patterns in stress management, motivation, and turnover intention. The study's contribution is interpretive, presenting a context-rich, local theory of the dynamics of burnout and retention in the high-security sector. The results will provide a foundation for more humane and contextual HR interventions, going beyond quantitative metrics, to improve the well-being and operational effectiveness of Critical Description Troops.